Phacoemulsification in Post Vitrectomy Eyes; Result and Complications - Widya Anandita; Syska Widyawati (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2018)
Introduction : To evaluate visual outcome and complication rate of phacoemulsification in post vitrectomy eyes. Methods : retrospective descriptive study Result : Data from seventy-five eyes was analyzed. Mean BCVA improves from 1.8 LogMAR (0.2- 2.5) to 1.3 LogMAR (0-2.5) postoperatively, with biggest improvement of 0.57 LogMAR shows in patients with preoperative BCVA of <1.8 LogMAR. Only 1.3% patient has intraoperative complication, and 52% patient has postoperative complication, of which 27.9% is PCO. Patients with silicon oil who underwent combination surgery of phacoemulsification and silicon oil extraction has higher redetachment rate (33%) compare to patient who only underwent phacoemulsification (20%). Conclusion : Phacoemulsification improves BCVA in most patients, and intraoperative complications rate was low. There was evidence of correlation between higher redetachment rate and combination of phacoemulsification with silicon oil extraction.